Framing and identity: how mainland and Taiwan media represent terrorist attacks in China? - Yan, Wang (2017)
Loss of identity is a leading cause of terrorism and a common bewilderment of Mainland China and Taiwan.Cutting into the research by the news representation of Chinese terrorism incidents, this paper discusses a special identity issue in a special identity history.This paper adopts mixed methods, which are constructed by content analysis, framing discourses and frequency statistics.111 pieces of related news are selected and doubly-coded into both “identity package” and “news framing”.The results show that the news representations inter-connect with the coexisting identity and confrontation between Mainland China and Taiwan.